Isolation of Murine Pancreatic Stellate Cells and the Establishment of a New ex-vivo Activation Model - Wang X; Li M; Liu X; Sun G; Zhang D; Sun L; Yin Y; Zhang W; Hao J (Clinical and Experimental Gastroenterology)
Xinye Wang,1,* Miaomiao Li,1,* Xinjuan Liu,1 Guangyong Sun,1,2 Dong Zhang,1,2 Lijun Sun,3 Yue Yin,4 Weizhen Zhang,3 Jianyu Hao1 1Department of Gastroenterology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of China; 2Medical Research Center, Beijing Institute of Respiratory Medicine and Beijing Chao-Yang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of China; 3Department of Physiology and Pathophysiology, School of Basic Medical Sciences, and State Key Laboratory of Vascular Homeostasis and Remodeling, Peking University, Beijing, 100191, People’s Republic of China; 4Department of Pharmacology, School of Basic Medical Sciences, and State Key Laboratory of Vascular Homeostasis and Remodeling, Peking University, Beijing, 100191, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianyu Hao, Department of Gastroenterology, Beijing Chao-Yang Hospital, Capital Medical University, No. 8, South Road of Workers Stadium, Chaoyang District, Beijing, 100020, People’s Republic of China, Email haojianyu@ccmu.edu.cn Weizhen Zhang, Department of Physiology and Pathophysiology, School of Basic Medical Sciences, and State Key Laboratory of Vascular Homeostasis and Remodeling, Peking University, No. 38, Xueyuan Road, Haidian District, Beijing, 100191, People’s Republic of China, Email weizhenzhang@bjmu.edu.cnBackground: Pancreatic stellate cells (PSCs) are critical in the development of pancreatic fibrosis. In vitro, cell attachment itself can promote cell activation. Currently, there is a lack of methods for isolating activated PSCs that are unaffected by cell attachment. This study aims to identify effective methods for isolating quiescent and activated murine PSCs (mPSCs) and to evaluate the potential of caerulein in inducing mPSC activation in an ex vivo model.Methods: Pancreatic tissue from mice was digested with collagenase P (1.17 U/mL), Pronase (0.5 mg/mL), and DNase I (0.01 mg/mL). Quiescent and activated mPSCs were isolated using a Nycodenz gradient. Immunostaining for α-smooth muscle actin (α-SMA), Desmin, glial fibrillary acidic protein (GFAP), vimentin, CK19, and CD68 was performed to confirm cell purity. Real-time quantitative PCR (RT-PCR) and RNA sequencing assessed the activation phenotype following caerulein treatment.Results: Quiescent and activated mPSCs were successfully isolated using the Nycodenz gradient, with cells exhibiting typical stellate morphology and positive staining for α-SMA, Desmin and vimentin. Oil Red O staining confirmed lipid droplets in quiescent mPSCs. In the caerulein-treated group, mPSC activation was significantly greater than in the saline-treated control group. RT-PCR revealed progressive upregulation of acta2 (**p< 0.01, d4 compared to d2, ##p< 0.01,d7 compared to d4,**p< 0.01,d7 compared to d2), col1a (**p< 0.01, d4 compared to d2,**p< 0.01,d7 compared to d2), and actg2 (**p< 0.01, d4 compared to d2, ##p< 0.01,d7 compared to d4, **p< 0.01,d7 compared to d2) mRNA levels at 2, 4, and 7 days post-adhesion. Fibroblast markers were also upregulated, and KEGG and GO enrichment analyses identified key pathways involved in ECM-receptor interactions, cell cycle regulation, PI3K-Akt signaling, and extracellular matrix remodeling.Conclusion: The Nycodenz gradient efficiently isolates quiescent mPSCs, and short-term caerulein treatment effectively activates mPSCs ex vivo, providing a valuable model for studying mPSC activation and related signaling pathways.Keywords: pancreatic stellate cells, chronic pancreatitis, pancreatic fibrosis